The Effect of Mulching and Planting Materials on the Growth and Yield of Sweet Potato (Ipomoea batatas L.) Sari Variety - Permanasari, Paramyta Nila; Putra, Rakha Alfyanda; Wicaksono, Karuniawan Puji; Guritno, Bambang (International Journal of Environment, Agriculture and Biotechnology, 2024)
The production of sweet potatoes (Ipomoea batatas L.) in Indonesia is still considered low compared to the national needs, which is approximately 2 million tons per year. Sweet potato yields can be improved by influencing both internal and external factors of the cultivation practices. The use of mulch has the potential to stabilize plants environment and growing condition. The use of different planting materials that has different characteristics and hormone contents will also influence the growth and yield of sweet potatoes. The aim of this study is to determine the interaction between the use of mulch and planting materials on sweet potatoes. The hypothesis of this research is that there will be an interaction between the two treatments, which could enhance yield. This research was conducted from February to May 2024 in Sidodadi Village, Garum Subdistrict, Blitar Regency. This study is a factorial experiment arranged based on a Randomized Block Design (RBD) consisting of 2 factors. The first factor is mulch with 3 levels: M0 (no mulch), M1 (silver-black plastic mulch) and M2 (rice straw mulch). The second factor is planting materials with 3 levels: T1 (upper shoot cuttings), T2 (middle shoot cuttings) and T3 (lower shoot cuttings). The results showed that the application of silver-black plastic mulch provided the best yield when applied together with upper shoot cuttings (28.40 tons ha-1), middle shoot cuttings (28.05 tons ha-1), and lower shoot cuttings (27.86 tons ha-1). The rice straw mulch treatment provided the best yield when applied together with upper shoot cuttings (22.53 tons ha-1) and middle shoot cuttings (21.68 tons ha-1). The treatment without mulch provided the best yield when applied together with upper shoot cuttings (25.79 tons ha-1). The choice of planting material can vary according to availability (upper, middle or lower of the shoot cutting) if using black silver plastic mulch.